Direct and Indirect Influences of Fate Control Belief, Gambling Expectancy Bias, and Self-Efficacy on Problem Gambling and Negative Mood Among Chinese College Students: A Multiple Mediation Analysis - Tang, C.S.-k. (2011)
10.1007/s10899-010-9177-1